Radical Prostatectomy in Kidney Transplant Recipients—A Multicenter Experience - Schmidt, Jacob; Yakac, Abdulbaki; Peters, Robert; Friedersdorff, Frank; Kernig, Karoline; Kienel, Anna; Winterhagen, Franziska I.; Köpp, Friedrich; Foller, Susan; DiQuilio, Francesca; Weigand, Karl; Flegar, Luka; et al. (European Urology Open Science, 2024)
Background and objective: Kidney transplant recipients (KTRs) have an increased risk of developing genitourinary cancers, including prostate cancer (PCa), which is expected to become more prevalent due to an aging KTR population. Thus, knowledge of surgical outcomes, including treatment of PCa, within this unique cohort is required. Methods: Data of 62 KTRs undergoing radical prostatectomy (RP) between 2006 and 2023 at nine urologic transplant centers were analyzed. Complications were assessed using the Clavien-Dindo classification. Perioperative outcomes were evaluated, and a follow-up was conducted. Overall survival (OS), biochemical recurrence–free survival (BRFS), and death-censored graft survival were determined via the Kaplan-Meier method and log-rank testing. Key findings and limitations: Overall, 50 open radical retropubic RPs and 12 robot-assisted RPs (RARPs) were included. The intraoperative blood loss was lower after RARP, but operative time was longer. Of the patients, 50% experienced no postoperative complication, and grade ≥3 complications were observed in 14.5%. There was no graft loss related to RP. A histopathologic analysis revealed pN1 in 8.1% and positive surgical margins in 25.8% of the cases. At a median follow-up of 48.5 mo, the median OS was 128 (95% confidence interval [CI] 71.2–184.8) mo, BRFS was 106 (95% CI 55.8; 156.2) mo, and graft survival was 127 (95% CI 66.7–187.3) mo. Limitations include the retrospective design, and variations between groups and centers. Conclusions and clinical implications: Our findings support RP as a feasible and safe treatment option for localized PCa in KTRs with acceptable oncologic outcome. Special care is required in screening and awareness for the risk of understaging. Patient summary: This study analyzed the safety and effectiveness of two prostate cancer surgery methods—open and robot-assisted surgery—in the special group of kidney transplant recipients. Both surgical methods were performed safely with acceptable oncologic outcomes; however, sample size was too small to draw definite conclusions between the two operative methods.
CRIS-Team Scopus Importer:2024-08-09
Keywords: Kidney transplantation; Open surgery; Prostate cancer; Prostatectomy; Robot-assisted surgery